Repurposed churches: an analysis through secularisation theory and the core-periphery model - Pettersson, Maria Grazia (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2024)
This study examines the repurposing of Anglican churches in the United Kingdom by integrating the core-periphery model developed by Friedmann and Krugman (UK) into secularisation theory, exploring how religious, cultural, and secular uses reflect broader social changes. With declining church attendance, many buildings are repurposed as homes, cultural monuments, or worship spaces for other faiths, such as free churches or mosques. The theory is tested by comparing several possible reuses for closed Anglican churches in the UK: conversion into homes, monuments, or mosques. The method utilised is a literature review, using data from local newspapers and reports by the Church of England and bodies responsible for monument protection. The result is a multi-dimensional approach similar to Wohlrab-Saar & Burchardt’s concept of multiple secularities, capable of assessing both the conversion of a sacred space into a profane space (a privatised or commercial actor, a public or a cultural space) and the transformation of a Christian/Anglican sacred space into a Muslim or free church sacred space. The findings indicate that many churches have been repurposed into homes and mosques, showing that market forces and individualisation have replaced religion and also revealing the emergence of diverse religious forms. This multidimensional approach suggests a pluralistic view of secularization, where secular and religious expressions co-exist and evolve in contemporary society.